The Oxford Encyclopedia of Public Administration : Volume 1 (A-I) - Volume 2 (J-W) - Peters, B. Guy; Thynne, Ian (New York: Oxford University Press, 2022)
"Public administration is a sprawling, diverse field that contains elements of political science, economics, law, sociology, ethics, and many other disciplines while also comprising issues and approaches distinctive to public administration. The Oxford Encyclopedia of Public Administration comprehensively examines the full range of concerns surrounding the core question of governance through administration. It provides significant theoretical perspectives, along with comprehensive assessments of the alignments of people, systems, and action, capturing the rich interconnectedness of public administration, policy, and governance. Contributors have been selected to reflect the diverse international community of scholars in this field, providing a wide range of insights into public administration as the enduring basis on which public affairs are arranged and managed. The 90 essays in this Encyclopedia fall into four main categories: Theoretical Approaches & Research; People in Public Administration; Systems & Instruments of Public Administration; and Public Administration in Action. The Oxford Encyclopedia of Public Administration is a critical resource for scholars, professionals, and students involved in the study, research, or practice of public administration"--
v. 1. The OE of public administration -- v. 2. The OE of public administration
Includes bibliographical references and index.
Keywords: Public administration -- Encyclopedias